Nucleation and growth mechanisms of nano-scaled Si precipitates in Al-7Si supersaturated solid solution. (5th May 2017) - Liu, Maowen; Fu, Hui; Tian, Lixi; Xiao, Wenlong; Peng, Qiuming; Ma, Chaoli
Abstract: A dense uniform distribution of nano-scaled Si precipitates has been achieved in Al-7Si alloy by high pressure solution treatment (HPST) and aging treatment. Precipitation behavior of Si phase was investigated using transmission electron microscopy (TEM). The results reveal that Si clusters initially precipitate from the Al(Si) solid solution, providing preferable nucleation sites for the equilibrium Si phase. The Si crystals exhibit spherical shape at first, and then grow rapidly parallel to 111Si planes. The shortage of growth ledges on 111 interfaces leads to the inhibition of growth perpendicular to these planes, which results in Si triangles and platelets with high aspect ratio. An equation about the relationship between the relative free energy and the equilibrium ledge densities on Al-Si interfaces was proposed. Graphical abstract: Highlights: Large amounts of nano-scaled Si crystals were achieved by high pressure solution treatment and aging treatment. Ledge growth of Si precipitates was directly observed by TEM in Al(Si) solid solution. Relationship between the Gibbs free energy and ledge density on Al/Si interfaces was quantitatively developed.